Cytokinin modulates the metabolic network of sulfur and glutathione. (13th October 2022) - Pavlů, Jaroslav; Kerchev, Pavel; Černý, Martin; Novák, Jan; Berka, Miroslav; Jobe, Timothy O; López Ramos, José Maria; Saiz-Fernández, Iñigo; Rashotte, Aaron Michael; Kopriva, Stanislav; Brzobohatý, Břetislav
Abstract: The phytohormone cytokinin is implicated in a range of growth, developmental, and defense processes. A growing body of evidence supports a crosstalk between cytokinin and nutrient signaling pathways, such as nitrate availability. Cytokinin signaling regulates sulfur-responsive gene expression, but the underlying molecular mechanisms and their impact on sulfur-containing metabolites have not been systematically explored. Using a combination of genetic and pharmacological tools, we investigated the interplay between cytokinin signaling and sulfur homeostasis. Exogenous cytokinin triggered sulfur starvation-like gene expression accompanied by a decrease in sulfate and glutathione content. This process was uncoupled from the activity of the major transcriptional regulator of sulfate starvation signaling SULFUR LIMITATION 1 and an important glutathione-degrading enzyme, γ-glutamyl cyclotransferase 2;1, expression of which was robustly up-regulated by cytokinin. Conversely, glutathione accumulation was observed in mutants lacking the cytokinin receptor ARABIDOPSIS HISTIDINE KINASE 3 and in cytokinin-deficient plants. Cytokinin-deficient plants displayed improved root growth upon exposure to glutathione-depleting chemicals which was attributed to a higher capacity to maintain glutathione levels. These results shed new light on the interplay between cytokinin signaling and sulfur homeostasis. They position cytokinin as an important modulator of sulfur uptake, assimilation, and remobilization in plant defense against xenobiotics and root growth. Abstract : Cytokinins induce transcriptional changes similar to sulfate starvation response and modulate the contents of sulfur-containing metabolites.